Electrical decarbonization technology as a replacement for equipment and appliances to reduce the burning of fossil fuels in civil buildings - Chavarry Vallejos, Carlos Magno; Chavarría Reyes, Liliana Janet; Támara Rodríguez, Joaquín Samuel; Pereyra Salardi, Enriqueta; Valencia Gutiérrez, Andrés Avelino; Zamora Terrones, Leydy Nataly; Pazos Sedano, Kelly Raquel (LACCEI, 2024)
The objective of this research is to implement electrical devices to reduce the burning of fossil fuels in civil buildings of the Fondo Mivivienda Program in Metropolitan Lima. Decarbonization aims to reduce or eliminate carbon dioxide (CO2) emissions contributing to climate change in buildings. Suitable electrical equipment was identified to manage effectiveness, productivity, and profitability, considering costs, time, and quality in real estate projects. The research follows a deductive method, quantitative approach, and has an applied, descriptive, correlational, and explanatory orientation. The design is non-experimental, cross-sectional, and prospective. The technique used is interviews with managers, engineers, and professionals involved in the design and technical aspects of the project. The data collection instrument was a semi-structured questionnaire with closed-ended and politomical value questions. The study revealed that decarbonization through electrification reduces CO2 emissions by 30.00%. Nationally, there is a 2.80% reduction in CO2 emissions and a 3.23% reduction in energy consumption. This reduction benefits costs, environmental quality, and user comfort.